The Tudor Domain-Containing Protein, Kotsubu (CG9925), Localizes to the Nuage and Functions in piRNA Biogenesis in D. melanogaster - Lim, Lin-Xenia; Isshiki, Wakana; Iki, Taichiro; Kawaguchi, Shinichi; Kai, Toshie (Frontiers in Molecular Biosciences, 2022)
Silencing of transposable elements (TEs) by Piwi-interacting RNAs (piRNAs) is crucial for maintaining germline genome integrity and fertility in animals. To repress TEs, PIWI clade Argonaute proteins cooperate with several Tudor domain-containing (Tdrd) proteins at membraneless perinuclear organelles, called nuage, to produce piRNAs to repress transposons. Here, we identify and characterize Kotsubu (Kots), one of the Drosophila Tudor domain-containing protein-1 (Tdrd1) orthologs, encoded by the CG9925 gene, that localizes to the nuage in gonads. We further show the dynamic localization of Kots in the male germline, where it shows perinuclear signals in spermatogonia but forms large cytoplasmic condensates in the spermatocytes that overlap with components of piNG-body, a nuage-associated organelle. The loss of kots results in a notable upregulation of stellate and a corresponding reduction in the suppressor of stellate piRNAs in the mutants. Furthermore, a moderate yet significant reduction of other piRNAs was observed in kots mutant testes. Taken together, we propose that Kots functions in the piRNA pathway, predominantly in the male germline by forming discrete cytoplasmic granules.